Nilai Pendidikan Karakter dalam Novel Ingkar Karya Boy Candra - Anggraini, Ririn; Rahayu, Sri (J-LELC: Journal of Language Education, Linguistics, and Culture, 2022)
The novel Ingkar Karya Boy Candra the researcher examines the value of character education which includes faith and piety, honesty, intelligence, toughness, caring contained in the novel. This research method is descriptive method. The technique used in this research is reading technique, note-taking technique and conclusion technique. research results show. The Value of Character Education in Boy Candra's Ingkar Novel in the aspect of Faith and Piety contains 9 data. The value of character education contained in the Ingkar Novel by Boy Candra in the Honesty aspect contained 7 data. The value of character education contained in the Ingkar Novel by Boy Candra in the Peduli aspect contained 10 data. The Value of Character Education in the Novel Ingkar Karya Boy Candra in the aspect of toughness there are 4 data and the value of character education contained in the Novel Ingkar Karya Boy Candra in the aspect of intelligence. Based on all the data, it is known that the value of character education contained in the novel Ingkar by Boy Candra was nominated by aspects of caring and faith and piety